Detection of deep fungal infections: a polyphasic approach - Sabino, Raquel (2019)
Purpose: Tissue samples from patients with suspicion of deep or subcutaneous fungal infections were analysed at the Portuguese Reference Mycology Laboratory according to a proposed diagnostic approach, which aims to constitute a rapid and accurate diagnosis for these fungal infections. Methodology: Forty-six tissue biopsy samples were analysed over a period of 26 months, using a diagnostic approach that includes culture, panfungal PCR and Aspergillus-directed PCR. Results/Key findings: Overall, 23 samples were reported as negative while the remaining 23 were reported as positive for fungi (PCR, culture and/or histology). PCR showed an estimated detection limit of 12 pg DNA µl–1. From the 46 samples, 30 were negative for fungal DNA while 16 gave positive results. From these, 12 cases were detected by panfungal PCR and six cases by PCR directed toward Aspergillus. In 61 % of the cases, there was concordance between molecular and cultural methods. Aetiological agents identified were Candida albicans, C. glabrata, C. tropicalis, Trichosporon montevideense, Alternaria spp., Exophiala sp., Trichoderma sp., Histoplasma spp., Aspergillus fumigatus, Trichophyton rubrum and Paracoccidioides brasiliensis. Conclusion: Our results showed that the proposed polyphasic approach appears to be a useful strategy in the detection of fungi from tissue samples, allowing a better prognosis. In further studies, the inclusion of a higher number of samples and the implementation of more genus-specific PCRs will certainly contribute to an increase in the specificity and sensitivity of this method.